The Role of Continuous Improvement Technology in Cost Reduction - Amjad Faiq, Haneen; Hameed Ali , Miaad (Journal of Economics and Administrative Sciences, 2024)
In recent years, many economic units have suffered losses as a result of a series of internal and external factors that led to an increase in their costs compared with expected revenues as a result of the use of high-cost materials, in addition to the environmental impacts as a result of their manufacturing waste ,To address this problem, the researcher used continuous improvement technology, used the Japanese approach, and identified high-cost raw materials. In addition to being harmful to the environment (copper, tin, antimony, and arsenic), to replaced with aluminum and calcium alloys, which in turn led to reducing battery costs and protecting the environment. The researcher conducted field work for the General Company for Automotive and Equipment Manufacturing (the factory Batteries) in the Babylon 2 laboratory with the aim of etermining the cost of the raw materials used in the manufacture of the battery and replacing them with other materials that are less expensive and less harmful to the environment , The researcher reached a set of results, the most important is that using continuous improvement technology leads to reducing costs and working to produce a safe product that does not danger to humans. And the environment, as well as using the Japanese approach of continuous improvement and replacing materials (copper, tin, antimony, and arsenic) with less expensive materials and less harmful to the environment, which leads to reducing environmental pollution and at the same time reducing costs. Paper type : Research Paper